Ameliorating effects of water bamboo shoot (Zizania latifolia) on acute alcoholism in a mice model and its chemical composition. (1st June 2022) - Gao, Yuan; Chen, Hangjun; Liu, Ruiling; Wu, Weijie; Mu, Honglei; Han, Yanchao; Yang, Hailong; Gao, Haiyan
Highlights: Water bamboo shoot (WBS) shows free radical scavenging and ADH activation activities. The alkali extract of water bamboo shoot alleviated acute alcoholism in mice. Butyl isobutyl phthalate and ferulic acid methyl ester might be the major compounds. Abstract: In this study, the ameliorative effect of water bamboo shoot (WBS) on acute alcoholism mice was investigated and potential biological compounds were explored. Results showed that extraction methods significantly affected the active substances contents and bioactivities of WBS. Principal component analysis (PCA) showed that alkali extract (NE) obtained the highest score, therefore, it was selected for further analysis . Animal experiments showed that NE demonstrated ameliorative effects on acute alcoholism mice as evident by significantly elevated activities of dehydrogenase (alcohol dehydrogenase, acetaldehyde dehydrogenase) and antioxidant enzymes (superoxide dismutase, glutathione peroxidase, catalase), whereas significantly reduced the levels of aminotransferase (alanine aminotransferase, aspartate aminotransferase) in serum. The potential bioactive activity compounds of NE were explored by UPLC-MS/MS and bioinformatics analysis. Butyl isobutyl phthalate vanillin, ferulic acid methyl ester might be the major compounds in NE on alleviating acute alcoholism. These results indicated that WBS possesses potential ameliorating effect on acute alcoholism.